Education and Innovation in The Management of Anemia Prevention for Pregnant Women By Giving "Camil Flower" Juice, Dragon Fruit Juice and Honey to Prevent Anemia in Pregnant Women - Azzahroh, Putri; Latifah; Aenurida; Reza Islamiati Soleha; Folorida, Tiurma; Marlinang Sihombing; Saripah Yuniar; Utami Megawati; Larontina Situmorang (International Journal of Community Services, 2024)
Abstract Background: Health issues receive serious attention from various elements of society. One way to overcome health problems in the community is to carry out community service. Community service is an activity that aims to help the community in several activities to overcome the problems they face by actively participating in the health development process and increasing community empowerment without expecting rewards in any form. Purpose: Carry out community service activities by carrying out activities ranging from secondary data collection to intervening and evaluating field activities. Method: Community midwifery practice carried out by Midwife Professional Education Students of National University Batch 6 Group 5 with practice areas at Yusma Medika Clinic which was carried out at Duren Jaya Health Center, Duren Jaya Village, East Bekasi District, Bekasi City, has been carried out with the following stages: Orientation, Secondary Data Collection, Focus Group Discussion (FGD), Planning Of Action (POA), Intervention activities in the form of counseling on "Camil Manise" (Prevent Anemia in Pregnant Women with nutritious foods and Fe supplements) as well as giving herbal drinks "Camil Flowers" (Dragon Fruit and Honey Prevent Anemia in Pregnant Women), and ended with Evaluation, Closing. Results: Community service activities in the form of counseling "Camil Manise" (Preventing Anemia of Pregnant Women with Nutritious Food and Fe Supplementation) and giving herbal drinks *Corresponding Author: Putri Azzahroh, Faculty of Health Sciences, National University, Jakarta, email: putriazzahroh@gmail.com "Camil Flower" (Dragon Fruit and Honey Prevents Anemia in pregnant women) is expected to make pregnant women understand more about anemia and can do proper prevention, one of which is by consuming herbal drinks dragon fruit and honey. Conclusion: Community service activities in the form of counseling young women about 'CAMIL MANISE' where health information is given on how to prevent anemia with nutritious food and Fe supplementation.